1989
DOI: 10.1557/proc-177-367
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Reaction Analysis Studies on the Interface Formation in Polymer Mixtures

Abstract: We have measured the composition profile between two polymer phases above and below their critical temperature for phase separation Tc, using the 2H(3He,4He)1H nuclear reaction in a direct profiling technique. Above Tc, we verify the “thtrmodynamic slowing down” effects on interdiffusion close to the critical point. Pelow Tc, we find that the width of the interface grows with time to a finite limiting value. The variation of this limiting value, as Tc, is approached from below is in good agreement with the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The technological significance of interdiffusion has driven a large number of experimental [5][6][7][8][9][10][11][12][13][14][15][16] and theoretical 12,[17][18][19][20][21][22][23] studies. Some of the these studies investigated interdiffusion of short oligomers below the entanglement length N e .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The technological significance of interdiffusion has driven a large number of experimental [5][6][7][8][9][10][11][12][13][14][15][16] and theoretical 12,[17][18][19][20][21][22][23] studies. Some of the these studies investigated interdiffusion of short oligomers below the entanglement length N e .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Other studies have focused on interdiffusion for two entangled polymers, for which both are much longer than the entanglement length N e . 5,6,9,11,12,[17][18][19]22,23 Kramer et al followed the diffusion of Au nanoparticles markers which were initially placed at the interface between two monodispersed entangled polystyrene (PS) films. 5 They found that the displacement of the markers scaled with time t as t 1/2 , in agreement with Fickian diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations